State of emergency under the Constitution of the Republic of Iraq 2005 Solutions and Treatments - صالح ماهر فيصل; عبدالله انتصار حسن; خليل مصطفى طلاع (Journal of Legal Sciences, 2019)
The emergency law is an exceptional system intended to support the executive authority with possibilities which limits the rights and freedoms of individuals to meet emergency conditions that threaten the public safety or country security, accordingly, the authority set forth in this law shall comply with the purpose set for it in taking any of the procedures provided by that law and does not depart from the means that are consistent with the constitution provisions. The reasons and conditions for declaring a state of emergency must be clear and stipulated in the constitution or in the emergency law in order to restrict the executive authority, the procedures implemented by the government under the state of emergency are different according to the existing constitutional system both in terms of their scope and the manner in which they are exercised in accordance with those texts, as for the successive constitutions and laws of Iraq, it did not take a single course in dealing with the authority to declare a state of emergency.